The employees' perceptions towards whistle -blowing in Nigeria - Garba, Mohammed Jamil (2023)
Whistleblowing has become an increasingly important topic in Nigeria, particularly in the context of combating corruption and promoting transparency within organizations. The aim of this study is to investigate the Employees perceptions on whistleblowing in Nigeria investigating the intricate dynamics surrounding whistleblowing perceptions within organizational contexts, focusing on the employees in Nigeria. A total number of 357 sample employees were chosen from 5000 populations using Kreiji and Morgan table was selected in which 319 employees responded to the questionnaire in Abuja Nigeria. Statistical Package software for Social Science (SPSS) Version 23 was used to analyse the descriptive analysis of the data. The smart Pls was used to test the reliability and validity of the data as well as the hypothesis. The study explores three key dimensions: the relationship between organizational culture and whistleblowing perception, the influence of trustful leadership, and the impact of well-defined policies and procedures and also mediating role of organizational justice. Findings reveal a nuanced or indirect relationship between organizational culture and whistleblowing, influenced by situational context and personal considerations. Trustful leadership is identified as a significant positive influence on employees' perceptions of whistleblowing, fostering a culture of openness and accountability. Additionally, clear policies and procedures are directly associated with favorable attitudes toward whistleblowing, establishing transparency and accountability. The research further delves into the mediating role of organizational justice, emphasizing its substantial influence on shaping positive attitudes toward whistleblowing. These findings contribute to a comprehensive understanding of the multifaceted nature of whistleblowing perceptions, highlighting the crucial role of organizational support and effective leadership in fostering a culture that encourages ethical reporting.